Enzymatic polymerization derived engineered polysaccharides as reinforcing fillers of ethylene vinyl acetate composites. (1st August 2020) - Mekonnen, Tizazu H.; Behabtu, Natnael; Lenges, Christian
Highlights: Monomer based enzymatic polymerization can be employed to produce polysaccharides. Structural polysaccharides provide reinforcing behavior in biocomposites. Polysaccharides demonstrate good compatibility with ethylene vinyl acetate (EVAs). Abstract: A novel monomer based, controlled enzymatic polymerization was employed to produce an engineered alpha-1, 3 glucan polysaccharide. The structure and material properties of the engineered polysaccharide were characterized using various techniques. The use of such engineered polysaccharide as a reinforcing filler of polymers was evaluated using model polymers. For this, the alpha-1, 3 glucan was incorporated into ethylene vinyl acetate co-polymer (EVA) matrices with vinyl acetate content of 32% and 40% via a melt processing fabrication process. Various mechanical and rheological properties of the fabricated composites were evaluated. The effect of vinyl acetate content of the EVA resin on the interaction with alpha-1, 3 glucan that result in various performances attributes was also investigated and reported. The incorporation of alpha-1, 3 glucan in these EVA composites resulted in the improvement of key composite properties, such as toughness, modulus, wear resistance, and hardness showing the reinforcing potential of these engineered polysaccharides.